Exploring the effect of wilting on fermentation profiles and microbial community structure during ensiling and air exposure of king grass silage - Chen, Rong; Li, Mao; Yang, Jinsong; Chen, Liwei; Zi, Xuejuan; Zhou, Hanlin; Tang, Jun (Frontiers in Microbiology, 2022)
In order to better understand the effect of wilting treatment on silage, we study analyzed the fermentation quality of unwilted (CK) and wilted (WT) king grass silage, and the dynamic changes of microorganisms in silage and aerobic exposure. After 30 days of silage, WT silage significantly reduced the pH of the silage (P < 0.05) and increased the contents of lactic acid and acetic acid (P < 0.05), but did not reduce the content of Ammonia-N (P > 0.05). Wilting treatment increased bacterial and fungal diversity during silage but decreased fungal diversity during aerobic exposure. The relative abundance of Lactococcus and Enterococcus in wilting silage increased. In the aerobic exposure stage, the relative abundance of Klebsiella decreased, but the relative abundance of Enterobacter increased in wilting treatment silage. In addition, the relative abundance of Acinetobacter and Ignatzschineria increased after 5 days of aerobic exposure. In contrast with unwilted silage, wilting treatment silage after aerobic exposure had no Candida, but the relative abundance of Wickerhamomyces increased. The results showed that wilting treatment could raise the silage quality of king grass. However, WT silage did not inhibit the reproduction of harmful microorganisms during aerobic exposure and did not significantly improve the aerobic stability of silage.